THE IMPACT OF NEW AGE MUSIC AS TREATMENT TO REDUCE STRESS - Henny Regina Salve (Jurnal Psikologi, 2007)
New Age music is the same as Alternative music. The term New Age take various forms and directions. This music draws on some of the flow of the music on this list, temasuk Ambient, Minimalism, Native American, Drum and Percussion, World, Electronic, Celtic, and Alternative. In music also use this technique entrainment and binaural beats. Entrainment is a principle in physics and is defined as the synchronization of two or more rounds rhythm (synchronization of two or more cycles rhytmic). The principle of this special can be used to create a resonance or synchronization in the brain of a specific frequency. While binaural beats found in 1939 by German eksperimenter HW Dowe. Human ability to "hear" binaural beats appears to be the result of the evolution of adaptation. Some species can detect binaural beats because otaknya structure. Frequency binaural beats that can be detected very depending on the size of the shell species. In the human, binaural beats can didetekdi at approximately below 1500 Hz (Oster, 1973 in Atwater 2004). Problems of relevance is the ability to detect congenital brain difference in phase between the ears to the perception of encouraging binaural beats (Atwater 2004). This research is a research experiment with the 18 people subject to the control group and 27 groups of people to experiment. For the experiment group, space is the space that used audio visual Gunadarma University. Meanwhile, New Age music used was the work of Peaceful Place Ken Davis. By using the seven-speaker, which consists of four large speakers, two speakers and one medium-sized speaker is small. This experiment appeared to be significantly lower level of stress in the experimental group.Key Words: New Age Music, Stress